Notions of Reliability - Adams, S. A.; De Bont, A. A. (Methods of Information in Medicine, 2003)
Objectives: This article analyzes the efforts of three organizations to provide a standard that guides Internet users to reliable health care sites.Methods: Comparison of health Internet sites, interviews and document studies.Results: In comparing these approaches, three different constructions of reliability are identified.Conclusions: The resulting possibilities and restrictions of these constructions for users that are searching for health information on the Internet are revealed.
Keywords: Internet user; health care; reliability; Internet health sites; qualitative research methods